2011
DOI: 10.1016/j.lindif.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Are success and failure experiences equally motivational? An investigation of regulatory focus and feedback

Abstract: a b s t r a c tThe present study extended regulatory focus theory to an educational setting and attempted to identify individuals with high motivation after both success and failure feedback. College students in Hong Kong (N = 180) participated in an experiment with a 2 promotion focus (high vs. low) × 2 prevention focus (high vs. low) × 2 feedback (success vs. failure) design. The results showed that after success feedback, the students with promotion focus were more motivated than their counterparts with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
0
22
3
Order By: Relevance
“…Namely, it is the negative feedback that increased motivation much more than the positive feedback. Aforementioned results gained additional confirmation in a recent study of Shu & Lam (2011) and Jarzebowski, Palermo, and Van de Berg (2012).…”
Section: Promotion Vs Prevention Orientationmentioning
confidence: 62%
“…Namely, it is the negative feedback that increased motivation much more than the positive feedback. Aforementioned results gained additional confirmation in a recent study of Shu & Lam (2011) and Jarzebowski, Palermo, and Van de Berg (2012).…”
Section: Promotion Vs Prevention Orientationmentioning
confidence: 62%
“…Granted, some cadets might experience increased motivation to perform better if they receive an F for a 66.9% on WPR1 in PL100, but others may not. Shu and Lam (2011) found that success and failure feedback was differentially motivating for students who were high vs. low in a desire to achieve positive outcomes or to prevent negative outcomes. Students who were high in the desire to attain positive outcomes were highly motivated after success feedback but not failure feedback, while students high in the desire to prevent negative outcomes were more highly motivated after failure feedback.…”
Section: Assessment Of Options and Implicationsmentioning
confidence: 96%
“…Attainment value therefore also predicts effort and determination [17,18]. Value is sometimes equated as a combination of the value of the input (i.e., costs) plus the value of the output.…”
Section: Expectancy Theorymentioning
confidence: 99%